2007
DOI: 10.2105/ajph.2006.100271
|View full text |Cite
|
Sign up to set email alerts
|

The Prophylactic Extraction of Third Molars: A Public Health Hazard

Abstract: Ten million third molars (wisdom teeth) are extracted from approximately 5 million people in the United States each year at an annual cost of over $3 billion. In addition, more than 11 million patient days of "standard discomfort or disability"--pain, swelling, bruising, and malaise--result postoperatively, and more than 11000 people suffer permanent paresthesia--numbness of the lip, tongue, and cheek--as a consequence of nerve injury during the surgery. At least two thirds of these extractions, associated cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
145
0
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(170 citation statements)
references
References 20 publications
2
145
0
18
Order By: Relevance
“…Furthermore, many orthodontists also propose the premature removal of ITM to stabilize the normal occlusion after completing the orthodontic therapy, and to prevent the late mandibular incisor crowding, a phenomenon related to the pressure exerted by erupting third molars. Even, some clinicians have proposed removing these teeth while they are still developing in jaw bone (7). However, different several single well-conducted clinical studies and systematic reviews have shown that there is scarce evidence to support all these assumptions or recommendations, and that it is almost impossible to predict whether an ITM will develop any pathological condition in the future (2-4, 7-9, 11, 13, 14, 17, 18, 21).…”
Section: Definition and Reasons For Prophylactic Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many orthodontists also propose the premature removal of ITM to stabilize the normal occlusion after completing the orthodontic therapy, and to prevent the late mandibular incisor crowding, a phenomenon related to the pressure exerted by erupting third molars. Even, some clinicians have proposed removing these teeth while they are still developing in jaw bone (7). However, different several single well-conducted clinical studies and systematic reviews have shown that there is scarce evidence to support all these assumptions or recommendations, and that it is almost impossible to predict whether an ITM will develop any pathological condition in the future (2-4, 7-9, 11, 13, 14, 17, 18, 21).…”
Section: Definition and Reasons For Prophylactic Extractionmentioning
confidence: 99%
“…According to Friedman, ten million third molars are extracted in the US each year, with an annual cost of over $3 billion (7); while in England and Wales, expenditures for the same reason amounted to around £ 5.2 million between 1995 and 1996 (4). So, third molar surgery generates significant income for dental professionals, particularly for oral and maxillofacial surgeons (7).…”
Section: Introductionmentioning
confidence: 99%
“…The controversy in the treatment of third molars is oriented philosophical currents of professional interventionists who are in favour of prophylactic removal of third complete and/or partially impacted molars symptom -free gives some pathology, covered in the indications for avoid a number of complications, however there is no scientific evidence to affirm or deny that all these procedures promote health patient [91,[97][98][99] .…”
Section: Introductionmentioning
confidence: 99%
“…[99] The triangular incision posterior to the second molar facilitate the vision of the site and also access to the bone region, and a better location for the side that would serve as a natural site drainage oblique incision. This oblique incision was started at the angle distobuccal the second molar and descends to the bottom of the groove (Figures 25 and 26).…”
Section: Introductionmentioning
confidence: 99%
“…Ten million teeth are extracted from approximately five million individuals every year in the United States alone, with an annual cost of over US$3 billion. 1 In England and Wales, expenditures on prophylactic extractions between 1995 and 1996 amounted to approximately £5.2 million. 2 The reason for these extractions is the high incidence of impaction, often associated with a number of oral problems, such as pericoronitis, periodontal defects in the distal region of the second molar, caries in the third or second molars, different types of odontogenic cysts and tumors, and crowding of the lower incisors.…”
Section: Introductionmentioning
confidence: 99%